(untitled) (Ta’limning zamonaviy transformatsiyasi, 2025)
Building an optimal safety framework involves the involvement and participation of various areas of lawmaking and activity, namely, the system of state regulation, which involves the distribution of the scope of powers of controlling and accountable state and local authorities, licensing of potentially dangerous activities, building and optimizing the system of standards for permissible pollution, creating a base of administrative responsibility and penalties at the level of offenses and others